PENGEMBANGAN MEDIA LAYANAN INFORMASI BERBASIS FLIPBOOK SEBAGAI PENCEGAHAN KEKERASAN SEKSUAL PADA SANTRI PESANTREN NURUL HUDA CIREBON - Henki, Dahabid; Amalia, Ulfa; Rossydah, Soffa (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Cases of sexual violence in pesantren are still an iceberg phenomenon that only seems to be the peak, in the sense that the case is still rarely revealed, not complained, not reported, or even often covered up for various reasons. Development of information services on sexual violence prevention in students in pesantren, the development of flipbook media aims to provide an understanding of sexual violence prevention in students in pesantren through guidance and counseling information services. This study used the Rnd (Research and Development) method with a research sample of 10 respondents who were students of Nurul Huda Islamic Boarding School Cirebon. Based on the results of the material validation test with a percentage of 90%, the results of the media validation test of 87% and user validation with the results of 81.5%, flipbook-based information services are said to be suitable for use by students or students as learning media